Implementation of Financing for Complete Systematic Land Registration (PTSL) Program in Sidayu Village, Batang Regency - Handayani, Wahyu Putri (Indonesian Journal of Agrarian Law, 2026)
A national project called the Complete Systematic Land Registration Program (PTSL) aims to provide legal certainty to the general public regarding their land rights. Its implementation at the village level is often hampered by funding issues that are not aligned with central regulations. The purpose of this study is to examine how PTSL funding is carried out in Sidayu Village, Batang Regency, and to identify the factors that influence the calculation of charges above the normative standard. The research method used was descriptive qualitative with a juridical-empirical approach. Primary data were obtained through interviews with 17 informants from village government elements, the Batang Regency Land Office, and the community. Secondary data were collected through documentary studies of regulations, internal committee documents, as well as program achievement data from the Batang Regency Land Office for 2022–2025. The study found a disparity in the PTSL preparation costs in Sidayu Village of IDR 350,000, exceeding the maximum limit of IDR 150,000 set in the 2017 Joint Regulation of 3 Ministers. This practice is influenced by the absence of a Regent Regulation, the topographical conditions of the area, and high field operational costs. The implication is that the principle of legal certainty is weakened because the determination of costs is only based on informal agreements without a valid regional legal basis. It is recommended that the Batang Regency Government immediately issue a Regent Regulation to provide legal legitimacy, transparency, and legal protection for both implementers and program participants.